Human Factors Advances in Naval Aviation Survival Training. (September 2021) - Milam, LT Chad; Anania, Emily; Keebler, Joseph; Atkinson, Beth
This panel will provide an overview of challenges and advances underway for aviation survival training. Navy instruction (Department of the Navy, 2019, CNAF M-3710.7) outlines a variety of training requirements that are addressed during aviation survival training. Two presentations will provide an overview of enhancements related to Dynamic Altitude Breathing Threats Training. For normobaric hypoxia training, presenters will provide an overview of a preliminary analysis of a software product designed to give students relevant tasking to complete while experiencing the effects of hypoxia in order to highlight symptoms. The next presentation, focused on dynamic altitude breathing threats training will provide an overview of differences identified between available training solutions from the perspective of both students and instructors. The third presentation will provide the preliminary results of a spatial disorientation curriculum analysis focused on identifying available technologies. The presentation will provide recommendations for how modernizing training in a way that provides increased training effectiveness for aviators. The fourth and final presentation will provide an overview of parachute training, including a review of training objectives and results of a market research analysis, as well as an outline of an upcoming training effectiveness evaluation of existing training solutions.